2012
DOI: 10.2967/jnumed.111.095224
|View full text |Cite
|
Sign up to set email alerts
|

Subregional Patterns of Preferential Striatal Dopamine Transporter Loss Differ in Parkinson Disease, Progressive Supranuclear Palsy, and Multiple-System Atrophy

Abstract: Parkinson disease (PD), progressive supranuclear palsy (PSP), and multiple-system atrophy (MSA) are known to affect dopaminergic neurons of the brain stem and striatum with different preferential involvement. Here we investigated differences in striatal subregional dopamine transporter loss in PD, PSP, and MSA and assessed the diagnostic value of 18 F-fluorinated-N-3-fluoropropyl-2-b-carboxymethoxy-3-b-(4-iodophenyl)nortropane ( 18 F-FP-CIT) PET in differentiating PSP and MSA from PD. Methods: Forty-nine patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
191
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(202 citation statements)
references
References 36 publications
8
191
1
2
Order By: Relevance
“…Already in early disease stages, patients initially diagnosed with PD that later converted to MSA or PSP have lower DAT binding in the caudate nucleus than patients in whom a diagnosis of PD is maintained (4). In addition, our findings in the posterior putamen in the ROI analysis corroborate the results of earlier studies by Oh and Messa (8,9). The automated DAT binding analyses resulted in comparable data, suggesting this type of approach is useful when assessing striatal binding in routine clinical practice.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Already in early disease stages, patients initially diagnosed with PD that later converted to MSA or PSP have lower DAT binding in the caudate nucleus than patients in whom a diagnosis of PD is maintained (4). In addition, our findings in the posterior putamen in the ROI analysis corroborate the results of earlier studies by Oh and Messa (8,9). The automated DAT binding analyses resulted in comparable data, suggesting this type of approach is useful when assessing striatal binding in routine clinical practice.…”
Section: Discussionsupporting
confidence: 82%
“…Several previous studies have demonstrated lower overall striatal DAT binding in PSP and MSA-P than PD, with relative sparing of the caudate nucleus in PD (4,8,9,14). Already in early disease stages, patients initially diagnosed with PD that later converted to MSA or PSP have lower DAT binding in the caudate nucleus than patients in whom a diagnosis of PD is maintained (4).…”
Section: Discussionmentioning
confidence: 95%
“…PSP subjects exhibited significant reductions in DAT binding involving both caudate and putamen, 37 which resulted in higher (more ''normal'') putamen/caudate ratio values relative to the LBD groups. This was consistent with early dopaminergic imaging findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, CT images have limitations in PET quantification in the brain structures due to the lack of softtissue differentiation. In brain PET imaging, 18 F-fluoropropylcarbomethoxyiodophenylnortropane ( 18 F-FP-CIT) has been widely used for evaluation of Parkinsonian syndrome as dopaminergic system imaging (3,4). For quantification of dopamine transporter (DAT) density, manually drawn regions of interest or softwarebased coregistered additional MR images have been used to overcome the issues regarding striatal segmentation (5-7).…”
mentioning
confidence: 99%